Examining the effect of Community Participation on Beneficiary Satisfaction with the work of Water Management Committee in Urban Community-Based Operated Water Schemes - Erick, O. Ananga; Stephen, G. Agong’; Michael, Acheampong; Ambe, J. Njoh; Patrick, Hayombe (Springer Nature, 2020)
Community participation (CP) has become popular in development discourse and practice, particularly in relation to water resource management. Greater involvement of beneficiaries in decision-making and implementation of water management practices is expected to increase efficiency and equity. However, the lingering question remains—Does CP necessarily result in outcomes of greater beneficiary satisfaction? Relatively little is known about the linkage. This article seeks to examine the relationship between community participation and beneficiary satisfaction with the work of the water management committee. Four urban-based community operated water schemes in the city of Kisumu, Kenya, are used as empirical referent. We applied quantitative research methodology by conducting a detailed survey and logistic regression analytic technique to analyze the data. We used seven parameters/indicators to operationalize participation and one to ascertain satisfaction with the work of the water management committee. Our results indicate that five participatory variables correlate with beneficiary satisfaction with the work of the water management committees including provision of labor (p < .05), willingness to intervene against vandalism (p < .05), meeting attendance (p < .05), financial contribution (p < .05) and payments of water bills on time (p < .05). These findings suggest that managers of community water supplies projects together with development partners need to encourage the identified participatory variables as a means of augmenting beneficiary satisfaction and most importantly improving effectiveness/sustainability.
Keywords: Urban-Based Water Schemes; Community Participation; Performance Factors; Sustainability; Developing Countries